(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This study examines the environmental impact of the fast fashion industry. It analyzes water consumption, energy use, microplastic pollution, and social consequences. The research evaluates clothing production processes — from cotton cultivation, synthetic fiber production, dyeing, and finishing — and their contributions to freshwater depletion, carbon dioxide emissions, and waste generation. Based on scientific literature, industry reports, and statistical data, the study demonstrates the scale of fast fashion’s environmental harm and discusses sustainable alternatives such as slow fashion, recycling, and eco-technology materials. Recommendations are provided to reduce the ecological and social impacts of fast fashion.